Optical excitations of Si by time-dependent density functional theory based on exact-exchange Kohn-Sham band structure - Kim, Y.-H.; Städele, Martin; Görling, Andreas (International Journal of Quantum Chemistry, 2003)
We calculate the imaginary part of the frequency-dependent dielectric function of bulk silicon by applying time-dependent density functional theory (TDDFT) based on the exact-exchange (EXX) Kohn-Sham (KS) band structure and the adiabatic local-density approximation (ALDA) kernel. The position of the E absorption peak calculated with the EXX band structure at the independent-particle level is in excellent agreement with experiments, which demonstrate the good quality of EXX "KS quasiparticles." The excitonic E peak that is missing at the independent-particle level remains absent if two-particle interaction effects are taken into account within the ALDA to TDDFT, demonstrating the incapability of the ALDA kernel to describe excitonic effects. © 2002 Wiley Periodicals, Inc. Int. J. Quantum Chem.